Delineating extrastriate visual area MT(V5) using cortical myeloarchitecture - Bridge, H; Clare, S; Krug, K (Elsevier, 2014)
Visual area MT is a model of choice in primate neurophysiological and human imaging research of visual perception, due to its considerable sensitivity to moving stimuli and the strong direction selectivity of its neurons. While the location of MT(V5) in the non-human primate is easily identifiable based on the gross anatomy and appears consistent between animals, this is less the case in human subjects. Functional localisation of human MT+ with moving stimuli can identify a group of motion-sensitive regions, but defining MT proper has proved more challenging. In this review we consider approaches to studying the cyto- and myeloarchitecture of this cortical area that may, in the future, allow identification of human MT in vivo based on anatomy.